ANALISIS PENGARUH STRATEGI INSTITUSI, BUDAYA INSTITUSI, DAN CONFLICT OF INTEREST TERHADAP BUDGETARY SLACK - N, Henrika C Tri Adi; Mardiasmo, Mardiasmo (Journal of Indonesian Economy and Business, 2002)
This study examines the influences of Institution Strategy, Institution Culture, and Conflict of Interest on Budgetary Slack. The culture was devided into two types; common culture, the employee working process and budget culture, the composing budget process. The results of the case study at Local Government in Daerah Istimewa Yogyakarta showed that institution culture tend to have positif influence on common culture, commitment organization, and locus of control. On the other hand, it was found that rewards for group performance, hierarchical index, philosophy, and supervisor as team leader have high influence for budgetary slack creating. Both interview and direct questionare fill up show that the budget is not enough for executive programs and projects due to misunderstandings that often happen between executive and legislative in the process of composing. Otherwise, the program will be dropped or cut down if the reason was not accepted or conformed by legislative. However, conflict of interest tend to have negatif influence on budgetary slack and institution strategy that hold up their work.Â Key Words: Institution Strategy, Institution Culture, Conflict of Interest, Budgetary Slack